2008
DOI: 10.1021/bp070481r
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Colorants: Characterization of Prodiginines and Their Applications on Textile Materials

Abstract: A strain of Vibrio sp. isolated from marine sediments produced large quantities of bright red pigments that could be used to dye many fibers including wool, nylon, acrylics, and silk. Characterization of the pigments by electrospray ionization mass spectrometry (ESI-MS) and nuclear magnetic resonance (NMR) revealed three prodiginine-like structures with nonpolar characteristics and low molecular mass. UV-visible spectra of the major constituent in methanol solution showed absorbance at λ max 530 nm wavelength.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
123
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 15 publications
(16 reference statements)
5
123
0
8
Order By: Relevance
“…This compound has shown significant biological potential due to its antimicrobial (3), antimalarial (4), anticancer (24), and immunosuppressive (14) activities. According to a recent report, prodigiosin or its analogues have been considered effective biological control agents against harmful algae (17,25), have been considered cell growth regulators (13), and can be used as a natural dye (1). On the other hand, it has been known that cycloprodigiosin (cPDG) is produced only as a minor compound by a few marine bacteria, including Pseudoalteromonas (Alteromonas) rubra, Pseudoalteromonas denitrificans, and Vibrio gazogenes (1,2,10,19).…”
mentioning
confidence: 99%
“…This compound has shown significant biological potential due to its antimicrobial (3), antimalarial (4), anticancer (24), and immunosuppressive (14) activities. According to a recent report, prodigiosin or its analogues have been considered effective biological control agents against harmful algae (17,25), have been considered cell growth regulators (13), and can be used as a natural dye (1). On the other hand, it has been known that cycloprodigiosin (cPDG) is produced only as a minor compound by a few marine bacteria, including Pseudoalteromonas (Alteromonas) rubra, Pseudoalteromonas denitrificans, and Vibrio gazogenes (1,2,10,19).…”
mentioning
confidence: 99%
“…Kulkarni et al [3] reported the application of yellow pigment in the dyeing of fabric produced by Kocuria flava sp. HO-9041 similarly application of bright red pigment prodigiosin for dying of wool, nylon, acrylic and silk had been suggested by Alihosseini et al [4] and Ahmed et al [5]. While Alcantara et al [6] have demonstrated the application of zeaxanthin from Flavobacterium sp in food as an additive in poultry feeds.…”
Section: Introductionmentioning
confidence: 95%
“…Recently prodiginines have again been attracting attention because they show a variety of bioactivities, antibiotic, anticancer, antimalarial, antiprotozoal, antifungal, immune-suppressive activities and so on. [13][14][15][16][17] The MIC of streptorubin B with MRSA N315 was more than or equal to 32 µg/mL, thus anti-MRSA activity is not strong. The biofilm formation of MRSA N315 was reduced to 27% at 1 µg/mL of streptorubin B. Biofilm formation was reduced to less than 50% even in the presence of 0.17 µg/mL, less than or equal to the 1/188 of the MIC.…”
Section: )mentioning
confidence: 99%
“…In a recent study, the application of prodiginines to textile materials such as wool, nylon and acrylic has been demonstrated. 14) We believe that there are more possibilities to prevent infections by utilizing these kinds of anti-infectious compounds.…”
Section: )mentioning
confidence: 99%